Identifying and Implementing Common Tactics to Disrupt IoT Device Functionality Over TCP/IP Stacks - Hajdu, Szabolcs; Kis, Gerlinda Boglarka; Fekete, Albert Zsombor; Kutasi, Denes Nimrod (IEEE International Symposium on Computational Intelligence and Informatics, 2024)
The proliferation of Internet of Things (IoT) devices in home automation systems has introduced unprecedented convenience but also raised serious concerns regarding security vulnerabilities [1]. This paper delves into the exploration of common vulnerabilities present in IoT-based home automation systems and proposes easily implemented solutions to disrupt their functionality. Through a comprehensive analysis of popular IoT devices, protocols, and communication channels, we identify key vulnerabilities that expose these systems to potential attacks, encompassing unauthorized access, data breaches, and device manipulation. Our findings contribute to the ongoing discourse on securing IoT devices and systems, emphasizing the need for proactive measures to safeguard user privacy, data integrity, and overall system reliability. By disseminating easily deployable solutions, we intend to foster a safer and more resilient environment for the growing landscape of IoT home automation.